2016
DOI: 10.3892/mmr.2016.5052
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of luteolin on memory impairment in an Alzheimer's disease model

Abstract: Alzheimer's disease (AD) is one of the most prevalent neurodegenerative disorder. It is characterized by the formation of amyloid plaques and neurofibrillary tangles in the brain, the degeneration of cholinergic neurons and neuronal cell death. The present study aimed to investigate the effect of luteolin, a flavonoid compound, on memory impairment in a streptozotocin (STZ)-induced Alzheimer's rat model. Morris water maze and probe tests were performed to examine the effect of luteolin treatment on cognition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 44 publications
1
71
0
Order By: Relevance
“…The onset and progression of AD is multifactorial. Underlying mechanisms that may lead to cognitive impairment involve cellular injury from β-amyloid (Aβ), tau, excitotoxicity, mitochondrial damage, acetylcholine loss, astrocytic cell injury, oxidative stress, and cellular metabolic dysfunction [ 10 20 ]. In light of the multiple pathways that may be responsible for the onset of AD, developing therapies are designed to focus on a variety of targets that include DNA methylation, deployment of monoclonal antibodies against Aβ, prevention of Aβ and tau aggregation, increased cytokine and growth factor signal transduction, mammalian target of rapamycin (mTOR) modulation, and the application of metal chelators [ 14 , 15 , 17 , 18 , 21 27 ].…”
Section: Assessing the Role Of Foxo Transcription Factors For Alzheimmentioning
confidence: 99%
“…The onset and progression of AD is multifactorial. Underlying mechanisms that may lead to cognitive impairment involve cellular injury from β-amyloid (Aβ), tau, excitotoxicity, mitochondrial damage, acetylcholine loss, astrocytic cell injury, oxidative stress, and cellular metabolic dysfunction [ 10 20 ]. In light of the multiple pathways that may be responsible for the onset of AD, developing therapies are designed to focus on a variety of targets that include DNA methylation, deployment of monoclonal antibodies against Aβ, prevention of Aβ and tau aggregation, increased cytokine and growth factor signal transduction, mammalian target of rapamycin (mTOR) modulation, and the application of metal chelators [ 14 , 15 , 17 , 18 , 21 27 ].…”
Section: Assessing the Role Of Foxo Transcription Factors For Alzheimmentioning
confidence: 99%
“…In addition, it has shown robust anti-inflammatory effects by reducing the production of LPS-induced pro-inflammatory cytokines in intestinal epithelial cells, mouse bone marrow-derived dendritic cells [ 21 ], rat fibroblasts [ 22 ], and human gingival fibroblasts [ 23 ]. Moreover, it has been demonstrated that luteolin exerted anti-amnesic effects against Aβ-induced toxicity [ 24 , 25 , 26 ]. In our previous studies, we demonstrated that the improvement in cognition and neuroprotective effects of luteolin included regulating microvascular function and protecting to BBB ultrastructure [ 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this direct anti-oxidant properties, luteolin was also reported to inhibit LPS-induced activation of NF-κB and MAPK pathways, but its mode of action was not understood 27 . Luteolin is blood-brain barrier permeable and was reported to have a neuroprotective effect in drug-induced Alzheimer’s rat model 38 . These properties would be therefore in line with a role for PKR in impairment of cognition through inflammation.…”
Section: Discussionmentioning
confidence: 99%